Night shift work and osteoporosis among female blue-collar workers in Poland - a pilot study. (2nd June 2020) - Bukowska-Damska, Agnieszka; Skowronska-Jozwiak, Elzbieta; Kaluzny, Pawel; Lewinski, Andrzej; Peplonska, Beata
ABSTRACT: Osteoporosis is an important public health problem worldwide. Although a number of factors that affect bone structure have been described; thus far, the current knowledge of occupational factors that may have an influence on bone tissue metabolism is strongly limited. Published studies indicate night shift work and the related circadian rhythm disruption may be considered as plausible underlying factors. The aim of the present study was to assess the potential association between night shift work and bone mineral density (BMD) among female blue-collar workers in Poland. A cross-sectional study was carried out among 194 female blue-collar workers >40 years of age employed in industrial plants. The operating system of work consisted of three work shifts clockwise rotation: morning (06:00–14:00 h), afternoon (14:00–22:00 h), and night (22:00–06:00 h), with five consecutive shifts per week followed by a free weekend. A questionnaire survey, based on a Polish version of The European vertebral osteoporosis study (EVOS) questionnaire, a validated instrument, was administered. Data on current job characteristics, job seniority, and lifetime duration of night shift work were also collected. BMD of the lumbar spine and hip (both total femur and femoral neck) was measured using dual-energy X-ray absorptiometry. Multivariate linear regression models were run, with bone mineralization parameters as dependent variables, as well as night work characteristics and important confounders. Statistical analysis was performed separately for premenopausal and postmenopausal women. The analyses adjusted for confounders did not reveal any significant differences between current or lifetime experience of night shift work and BMD among both premenopausal and postmenopausal women. However, the outcomes supported the well-established correlation with factors, such as age, BMI, and menopausal status. BMD at the three sites measured was significantly associated with BMI ( p < .001) and inversely associated with age ( p < .001) in the total study population. Postmenopausal women had significantly lower BMD than did premenopausal women ( p < .001). The study findings indicate that in the population of Polish female blue-collar workers, the system of work does not seem to be associated with the development of osteoporosis.